2013
DOI: 10.1186/1752-1947-7-142
|View full text |Cite
|
Sign up to set email alerts
|

‘Honeycomb appearance’ on three-dimensional transthoracic echocardiography as the landmark of left ventricular non-compaction: two case reports

Abstract: IntroductionLeft ventricular non-compaction is a rare congenital heart disease, and is most commonly diagnosed via two-dimensional echocardiography according to echocardiographic criteria. Recently, transthoracic three-dimensional echocardiography has become available in the clinical setting.Case presentationWe present two isolated cases of left ventricular non-compaction from Japan (in an 84-year-old woman and 47-year-old man) that were confirmed by two-dimensional echocardiography, contrast-enhanced two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Isolated left ventricular noncompaction has to be distinguished from prominent hypertrabeculation with a normal compact layer. 4 Konishi et al 7 have reported a diagnosis made on an 84-year-old woman and 47-year-old man on a 3D echocardiography where "honeycomb appearance" was considered as landmark in diagnosis of LVNC. Prenatal diagnosis of LVNC may be possible in a Barth syndrome (X-linked recessive inheritance), but in others, fetal scan may appear normal and the disease may present later in life.…”
Section: Discussion Cardiomyopathymentioning
confidence: 98%
“…Isolated left ventricular noncompaction has to be distinguished from prominent hypertrabeculation with a normal compact layer. 4 Konishi et al 7 have reported a diagnosis made on an 84-year-old woman and 47-year-old man on a 3D echocardiography where "honeycomb appearance" was considered as landmark in diagnosis of LVNC. Prenatal diagnosis of LVNC may be possible in a Barth syndrome (X-linked recessive inheritance), but in others, fetal scan may appear normal and the disease may present later in life.…”
Section: Discussion Cardiomyopathymentioning
confidence: 98%